Application of new technologies in decontamination of mycotoxins in cereal grains: Challenges, and perspectives. (February 2021) - Mir, Shabir Ahmad; Dar, B.N.; Shah, Manzoor Ahmad; Sofi, Sajad Ahmad; Hamdani, Afshan Mumtaz; Oliveira, Carlos A.F.; Hashemi Moosavi, Motahareh; Mousavi Khaneghah, Amin; Sant'Ana, Anderson S.
Abstract: Emerging decontamination technologies have been attracted considerable attention to address the consumers' demand for high quality and safe food products. As one of the important foods in the human diet, cereals are usually stored for long periods, resulting in an increased risk of contamination by different hazards. Mycotoxins comprise one of the significant contaminants of cereals that lead to enormous economic losses to the industry and threats to human health. While prevention is the primary approach towards reducing human exposure to mycotoxins, decontamination methods have also been developed as complementary measures. However, some conventional methods (chemical treatments) do not fulfill industries' expectations due to limitations like safety, efficiency, and the destruction of food quality attributes. In this regard, novel techniques have been proposed to food to comply with the industry's demand and overcome conventional methods' limitations. Novel techniques have different efficiencies for removing or reducing mycotoxins depending on processing conditions, type of mycotoxin, and the food matrix. Therefore, this review provides an overview of novel mycotoxin decontamination technologies such as cold plasma, irradiation, and pulse light, which can be efficient for reducing mycotoxins with minimum adverse effects on the quality and nutritional properties of produce. Graphical abstract: Image 1 Highlights: Many novel technologies of food processing have been explored for mycotoxin decontamination. These techniques have different mechanisms for degradation or removal of mycotoxins. Type of food matrix and processing conditions affect the degradation efficiency of mycotoxins. Ozone, cold plasma and irradiation have perspectives for mycotoxin degradation in food. Mycotoxin degradation or removal of bacteria and yeast have shown potential prospects.